The Effectiveness of Green Betel Leaf Decoction on Vaginal Discharge in Adolescent Girls at Al-Muhajirin Islamic Boarding School, Purwakarta Regency - Devita Zakirman; Rissa Irianti (Riviera Publishing, 2025)
Reproductive health issues throughout a woman's life cycle are diverse and complex. One common problem faced by women always is vaginal discharge. Vaginal discharge can cause itching, unpleasant odor, pain, and discomfort. This issue must be carefully monitored if it recurs, as it can lead to infertility and cancer. The research aims to determine the effectiveness of green betel leaf decoction on vaginal discharge in adolescent girls at Al-Muhajirin Islamic Boarding School, Purwakarta Regency in 2024. The research design is a plan arranged so the researcher can obtain answers to the research questions. This study uses a quantitative approach with a pre-experimental design, employing a one-group pretest-posttest format and a paired t-test. The paired t-test is appropriate because there is a single group measured twice, before and after treatment. The average vaginal discharge score in adolescents before administering green betel leaf decoction was 16.86, which decreased to 4.00 after treatment. The Wilcoxon test was used for statistical analysis, resulting in a p-value of 0.000. There was a significant effect before and after administration of green betel leaf decoction in reducing vaginal discharge among adolescent girls at Ma Miftahul Ulum Cikupa-Purwakarta in 2024. Out of 32 respondents, 21 experienced a decrease in vaginal discharge scores.